Implementasi Pembelajaran Pendidikan Agama Islam pada Anak Autis di Sekolah Luar Biasa Negeri Ciamis - Rahmawati, Reni; Firdaus, Anis Husni; Selamet, Selamet (Bestari, 2020)
This study aims to describe the learning outcomes of Islamic Religious Education for children with autism at the Ciamis Special School, namely as follows: 1) to determine the planning of Islamic Religious Education learning for children with autism in Ciamis State Special School; 2) to determine the implementation of Islamic Religious Education learning for children with autism in Ciamis State Special School; 3) to find out the evaluation of Islamic Religious Education learning for children with autism in Ciamis State Special School. This research uses a qualitative approach with a qualitative descriptive method. Collecting data using observation, interview, and documentation techniques. This research was conducted from March to May. The data sources were students with autistic special needs at the Ciamis Special School, while for complementary data the researchers conducted interviews and documentation studies. Then after the data is collected, it is followed by data reduction, presenting data, verifying data, and drawing conclusions. The results showed that: (1) Learning planning includes all aspects that support the implementation of the learning process. The learning process of PAI for children with autism in the Ciamis Special School School follows the 2013 curriculum with teacher modifications. The material presented is emphasized on practical material using various methods according to the needs of students. The learning process is guided by the educational components, namely: goals, educators, students, curriculum, materials, methods and evaluation, because all these components serve as benchmarks for adjusting the child's abilities, so that the desired learning objectives can be achieved. At the learning planning stage the teacher also prepares learning tools, namely the syllabus and lesson plans; (2) The implementation of Islamic Education learning for children with autism emphasizes character / moral education, various learning methods are used, tailored to the needs of students. The implementation of Islamic Education learning includes preliminary or apperception activities, core activities, and closing activities. The time allocation for the implementation is 2 hours of lessons (2x35 minutes) and is held every Thursday from 07.30 to 08.40 WIB; (3) The evaluation carried out at Ciamis State Special School is carried out in three activities namely case evaluation, semester program evaluation and follow-up. The PAI learning results show that autistic children experience development / progress in carrying out religious rituals, as well as in living behavior as demands of their religion. This is shown like ablution, prayer, daily prayers and so on. Assessment standards and minimum completeness criteria (KKM) scores are set by the school